Association between calcium intake, parathormone levels and blood pressure during pregnancy. (Colombia Medica, 2009)
Purpose: To evaluate the association between calcium intake from diet, calciotropic hormones (PTH, PTH-rp), vasoactive regulators (endothelin, nitric oxide) and blood pressure levels during pregnancy, birth and puerperium. Method: In a prospective study 149 healthy normotensive primigravidas were followed-up from 15 weeks of gestation to puerperium. Daily calcium intake, calciuria, PTH, PTH-rp, endothelin, nitrite-nitrate, and Holter Test were assessed. Linear regression models were performed to evaluate the association between calcium intake, blood pressure levels and the laboratory tests. Multivariate regression models were performed to control potential confounders. Results: A significant increase of calcium intake during pregnancy was observed (931±301 mg/day to 1,195±467 mg/day, p< 0.001). Plasma PTH-rp, endothelin, and nitrite-nitrate levels did not change during pregnancy. Among the women 38 (25.4%) had low calcium intake (< 800 mg/day) with a larger increase of systolic and diastolic blood pressure during pregnancy (p=0.04) birth (p=0.006) and puerperium (p=0.01). After adjusting for other factors the multivariate analyses showed statistical association between low calcium intake, high parathormone levels and high systolic blood pressure levels during pregnancy (p=0.002). Conclusion: Low calcium intake during pregnancy is associated with a larger increase of systolic blood pressure and high parathormone levels.